EXPERIMENTAL INVESTIGATION OF SVM SWITCHING CONTROLLER BASED TWO-LEVEL VOLTAGE SOURCE INVERTER FOR PHOTOVOLTAIC SYSTEM USING DSP-TMS320F28335 - Mutlag, Ammar Hussein; Mahdi, Siraj Qays; Mohammed Salim, Omar Nameer (COMPUSOFT: An International Journal of Advanced Computer Technology, 2017)
Many switching schemes can be utilized to control the voltage source inverter (VSI). The harmonic appears at the VSI output waveforms using any control schemes. The space vector modulation (SVM) seems to be more effective than the other switching schemes. Therefore, this paper presents an experimental investigation of SVM switching controller based two-level voltage source inverter (VSI) for photovoltaic system. The robustness of the proposed SVM is investigated with a hardware that is implemented via a DSP-TMS320F28335 controller. The experimental investigation is accomplished for the SVM in terms of total harmonic distortion (THD). Two types of loads are utilized which are resistive (R) load and resistive and inductive (RL) load to investigate the performance of the SVM. The results of the proposed SVM are compared with sinusoidal pulse width modulation (SPWM). The implementation of the SVM via a DSP-TMS320F28335 controller is verified in the laboratory using a prototype two-level SVI. The THDs based SVM are found to be 2.0% and 2.6% for the R and RL, respectively; whereas the THD based SPWM are found to be 2.2% and 3.1% for the R and RL, respectively. This indicates that high quality waveforms with low THD have been obtained with SVM.